2011
DOI: 10.1007/978-0-8176-8244-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Eigenvalue distributions and Weyl laws for semiclassical non-self-adjoint operators in 2 dimensions

Abstract: In this note we compare two recent results about the distribution of eigenvalues for semi-classical pseudodifferential operators in two dimensions. For classes of analytic operators A. Melin and the author [6] obtained a complex Bohr-Sommerfeld rule, showing that the eigenvalues are situated on a distorted lattice. On the other hand, with M. Hager [4] we showed in any dimension that Weyl asymptotics holds with probability close to 1 for small random perturbations of the operator. In both cases the eigenvalues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Indeed, in the analytic case there is the possibility to make an analytic distorsion (for instance by replacing the underlying compact analytic manifold by a small deformation) which will not change the spectrum (by ellipticity and analyticity) but which will replace the given real phase space by a deformation, likely to change the Weyl law. In one and two dimensions analytic distorsions have been used to determine the spectrum (by making the operator more normal) in the two-dimensional semi-classical case this was done by one of the authors, first with A. Melin, and in [8] it was shown that the resulting law is in general different from the Weyl law (naively because a complex Bohr-Sommerfeld law relies on going out in the complex domain while the Weyl law only uses the real cotangent space).…”
Section: Some Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the analytic case there is the possibility to make an analytic distorsion (for instance by replacing the underlying compact analytic manifold by a small deformation) which will not change the spectrum (by ellipticity and analyticity) but which will replace the given real phase space by a deformation, likely to change the Weyl law. In one and two dimensions analytic distorsions have been used to determine the spectrum (by making the operator more normal) in the two-dimensional semi-classical case this was done by one of the authors, first with A. Melin, and in [8] it was shown that the resulting law is in general different from the Weyl law (naively because a complex Bohr-Sommerfeld law relies on going out in the complex domain while the Weyl law only uses the real cotangent space).…”
Section: Some Examplesmentioning
confidence: 99%
“…-There is a constant C > 0 such that (4.7) holds with probability 8) and the α j are independent. Now, using standard functional calculus for R as in [9,10], we see that…”
Section: Semiclassical Reductionmentioning
confidence: 99%
“…In the paper [25], it has been shown that for large and stable classes of non-selfadjoint analytic operators in dimension two, the individual eigenvalues can be determined accurately in the semiclassical limit by means of a Bohr-Sommerfeld quantization condition, defined in terms of suitable complex Lagrangian tori close to the real domain. (See also [35] for the formulation of the corresponding Weyl laws.) The work [25] was subsequently continued in a series of papers [12]- [14], [16], [15], all of them concerned with the case of non-selfadjoint perturbations of selfadjoint operators of the form, P ε (x, hD x ) = p w (x, hD x ) + iεq w (x, hD x ), 0 < ε ≪ 1, with the leading symbol p ε (x, ξ) = p(x, ξ) + iεq(x, ξ), (x, ξ) ∈ T * R 2 .…”
Section: Introductionmentioning
confidence: 99%